2019
DOI: 10.1002/ece3.5386
|View full text |Cite
|
Sign up to set email alerts
|

The environmental and genetic determinants of chick telomere length in Tree Swallows (Tachycineta bicolor)

Abstract: Conditions during early life can have dramatic effects on adult characteristics and fitness. However, we still know little about the mechanisms that mediate these relationships. Telomere shortening is one possibility. Telomeres are long sequences of DNA that protect the ends of chromosomes. They shorten naturally throughout an individual's life, and individuals with short telomeres tend to have poorer health and reduced survival. Given this connection between telomere length (TL) and fitness, natural selection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 71 publications
0
21
1
Order By: Relevance
“…Studies in vertebrates have provided evidence for positive (e.g. Eisenberg et al., 2017; Kimura et al., 2008; Njajou et al., 2007), negative (summarized in table 1 in Belmaker et al., 2019; Eisenberg, 2019) or no (summarized in table 1 in Eisenberg, 2019) PAC effect, and positive (Asghar et al., 2015) or no (Bauch et al., 2019; Belmaker et al., 2019; Bouwhuis et al., 2018; Froy et al., 2017; Heidinger et al., 2016; McLennan et al., 2018) MAC effect on offspring telomere length. In cross‐sectional mammalian studies, positive PAC effects have been reported in humans, a negative PAC effect was found in a captive population of short‐lived house mice ( Mus musculus ; de Frutos et al., 2016), and in a wild population of longer‐lived Soay sheep there was no relationship between offspring RLTL (either measured across all ages or only as lambs) and PAC or MAC (Froy et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in vertebrates have provided evidence for positive (e.g. Eisenberg et al., 2017; Kimura et al., 2008; Njajou et al., 2007), negative (summarized in table 1 in Belmaker et al., 2019; Eisenberg, 2019) or no (summarized in table 1 in Eisenberg, 2019) PAC effect, and positive (Asghar et al., 2015) or no (Bauch et al., 2019; Belmaker et al., 2019; Bouwhuis et al., 2018; Froy et al., 2017; Heidinger et al., 2016; McLennan et al., 2018) MAC effect on offspring telomere length. In cross‐sectional mammalian studies, positive PAC effects have been reported in humans, a negative PAC effect was found in a captive population of short‐lived house mice ( Mus musculus ; de Frutos et al., 2016), and in a wild population of longer‐lived Soay sheep there was no relationship between offspring RLTL (either measured across all ages or only as lambs) and PAC or MAC (Froy et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Studies from different taxa, with a variety of mating systems, have shown a negative PAC effect (Bouwhuis et al, 2018;Criscuolo, Zahn, & Bize, 2017;Olsson et al, 2011), including a longitudinal (Bauch, Boonekamp, Korsten, Mulder, & Verhulst, 2019) and an experimental manipulation (Noguera, Metcalfe, & Monaghan, 2018) study. However, other studies have reported no PAC or MAC effect on offspring telomere length (Heidinger et al, 2016;McLennan et al, 2018;Froy et al, 2017;Belmaker, Hallinger, Glynn, Winkler, & Haussmann, 2019) or a positive MAC effect (Asghar et al, 2015). The variation in PAC and MAC effects on offspring telomere length among species requires more studies to disentangle potential causes and mechanisms underlying such variation in transgenerational effects.…”
Section: Introductionmentioning
confidence: 97%
“…For species with parental care, an extrapolation of this “telomere – individual quality hypothesis” is that parental telomere length may reflect parental quality, parents with longer telomeres being better at raising a large number of high‐quality offspring with high survival rates (i.e., “telomere – parental quality hypothesis”). Remarkably, because telomeres are genetic material passed on from parents to offspring, one topical question is the extent to which parent–offspring resemblance in telomere length is explained by genetic additive variance (heritability) and/or by other environmental effects caused by variation in the quality of pre‐ and posthatching parental care (Belmaker, Hallinger, Glynn, Winkler, & Haussmann, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Early studies suggested that telomere length is fixed in the zygote (i.e., inherited from the gametes in a sex‐ and age‐dependent way; Eisenberg, 2019), remaining unchanged for life relative to other individuals from the same cohort (Graakjaer et al., 2004). However, estimates of telomere length heritability appear to be largely variable across species (Asghar, Bensch, Tarka, Hansson, & Hasselquist, 2014; Atema et al., 2015; Becker et al., 2015; Belmaker et al., 2019; Stier, Reichert, Criscuolo, & Bize, 2015), suggesting that both genetics and environmental factors (including parental care) may influence offspring telomere length. However, assessing the effects of parental care quality on telomere length is complex, because it requires disentangling the contribution of additive genetic effects (i.e., heritability) from parental care per se on offspring telomeres.…”
Section: Introductionmentioning
confidence: 99%